1999
DOI: 10.1086/313166
|View full text |Cite
|
Sign up to set email alerts
|

Orbits of Five Visual Double Stars

Abstract: This paper revises and discusses the orbits and other parameters of the double stars WDS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…-This system has a grade 3 orbit 3 ( Docobo & Ling 1999). Astrometry computed from the orbital elements at the time of our observations, 2001.0985, gives a separation of 0.29 00 with a position angle of 244 .…”
Section: Known Binariesmentioning
confidence: 75%
“…-This system has a grade 3 orbit 3 ( Docobo & Ling 1999). Astrometry computed from the orbital elements at the time of our observations, 2001.0985, gives a separation of 0.29 00 with a position angle of 244 .…”
Section: Known Binariesmentioning
confidence: 75%
“…HD 37711 (WDS 05413+1632, BU 1007 ).-This system has a grade 3 orbit 3 ( Docobo & Ling 1999). Astrometry computed from the orbital elements at the time of our observations, 2001.0985, gives a separation of 0.29 00 with a position angle of 244 .…”
Section: Known Binariesmentioning
confidence: 82%
“…HD 37711 (126 Tau, HIP 26777) is a B-type star with a known visual companion. Docobo & Ling (1999) found a period of 115 yr for the highly eccentric orbit. Using speckle data compiled from WDS, Malkov et al (2012) confirmed this orbital period for the B8V+B7V system, with a high eccentricity of 0.87.…”
Section: Hd 37711mentioning
confidence: 98%